2013
DOI: 10.1371/journal.pone.0060835
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Enhanced Production of Foreign Recombinant Protein by Fusion with the Partial Polyhedrin of Nucleopolyhedrovirus

Abstract: To enhance the production efficiency of foreign protein in baculovirus expression systems, the effects of polyhedrin fragments were investigated by fusion expressing them with the enhanced green fluorescent protein (EGFP). Recombinant viruses were generated to express EGFP fused with polyhedrin fragments based on the previously reported minimal region for self-assembly and the KRKK nuclear localization signal (NLS). Fusion expressions with polyhedrin amino acids 19 to 110 and 32 to 110 lead to localization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…The recombinant viruses were generated using these vectors and named rAcPCV2ORF2, rAc-19-110-PCV2ORF2, and rAc-32-85T-PCV2ORF2, respectively. Although fusion of polyhedrin 19-110 increased the yield of recombinant PCV2 ORF2, it was lower than that of enhanced green fluorescent protein (EGFP) (Bae et al, 2013). These results corresponded to previous results that showed that fusion the control of the AcMNPV polyhedrin promoter (Fig.…”
Section: Enhanced Production Of Recombinant Capsid Proteinsupporting
confidence: 90%
See 2 more Smart Citations
“…The recombinant viruses were generated using these vectors and named rAcPCV2ORF2, rAc-19-110-PCV2ORF2, and rAc-32-85T-PCV2ORF2, respectively. Although fusion of polyhedrin 19-110 increased the yield of recombinant PCV2 ORF2, it was lower than that of enhanced green fluorescent protein (EGFP) (Bae et al, 2013). These results corresponded to previous results that showed that fusion the control of the AcMNPV polyhedrin promoter (Fig.…”
Section: Enhanced Production Of Recombinant Capsid Proteinsupporting
confidence: 90%
“…Recently, we demonstrated that the production of foreign proteins fused with various partial polyhedrin could enhance the production of foreign proteins significantly (Bae et al, 2013). Among various fused polyhedrin regions, fusions with amino acids 19-110 were able to localize the foreign proteins in the nucleus and enhance the expression level most highly.…”
Section: Construction Of Transfer Vectormentioning
confidence: 99%
See 1 more Smart Citation
“…At protein terminal level, hydrophilicity of histidine tag enhances the high solubility of expressed recombinant fusion proteins [8]. At protein level, polyhedrin is used as a carrier protein to facilitate antigen purification [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Polyhedrin has been used as a carrier protein to facilitate antigen purification [14-18]. This strategy for purification of antigen has been patented (see http://otl.sinica.edu.tw/en/index.php?t=9&group_id=19&article_id=477).…”
Section: Introductionmentioning
confidence: 99%